Pengaruh Penerapan Teknologi Informasi dan Kompetensi Auditor terhadap Kualitas Audit pada Kantor Akuntan Publik di Wilayah Jakarta Selatan - Lodiyanti Abuk Nahak; Eka Budi Yulianti; Desyi Erawati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the impact of the application of information technology and auditor competence on audit quality in Public Accounting Firms in DKI Jakarta. The focus of the research variables includes auditor competence as a key factor that affects audit quality. Based on the results of the SPSS v.25 test, the Influence of Information Technology and Competence simultaneously affects the Quality of Auditors in Public Accounting Firms in South Jakarta. This is shown by the value of the audit quality dependent variable simultaneously influenced by the Information Technology variable in this study, namely Information Technology and Auditor Competence. In this study, the results of data analysis obtained an R Square (R2) of 0.63.6 which means that the Audit Quality at Pubik Accounting Firms in DKI Jakarta is influenced by Information Technology and Competence. The rest is influenced by other variables that are not included in this study.